Uma proposta de sequência didática para o uso de invariantes na resolução de problemas - Zandonadi, Euzebio Glauder (2016)
This work is a didactic sequence for solving problems in the study of invariant, to be used with high school students. The themes are parity, divisibility, remainders, coloring and algebraic expressions. Each chapter has a contextualized theoretical development, followed by solved problems and proposed problems, as well as their answers and tips for the solution.